Distribusi perokok berdasarkan berbagai latar belakang demografi (Menurut data Susenas 2001 dan 1995) - Jamal, Sarjaini (Lembaga Penelitian Universitas YARSI, 2009)
Smoking habit is a pleasure for a person and may be dangerous for the others. The main ingredient of cigarette, kretek and cigar is tobacco. Tobacco has been known to contain a lot of chemical substances including nicotin, alkaloids, safrol, ammonia and tar whichare harmful to health. This study was carried out to depict smokers among community in any characteristics of demographic background. The data of smoking habit among peoples of 15 years old or above were collected from the National Health Survey (Survey Kesehatan Nasional) and Household Health Survey (SKRT) 2001 and 1995. More than 12.000 respondents had been interviewed. The result showed that during the last five years the proportion of smokers was increasing in all age groups among male but decreasing among female. Smokers were most prevalence in low educated population and in rural areas. The prevalence was also found to be higher in Sumatera compared to those in Java or eastern part of Indonesia. It is suggested that serious measures should be taken against the campaign of tobacco company including strengtheninglaw enforcement and enhance punishment to the people or company violating the tobacco regulation.